The great dinosaur hunters and their discoveries - Colbert, Edwin Harris, 1905-; Colbert, Edwin Harris, 1905- (New York : Dover Publications, 1984)
Describes the beginnings of dinosaur research in 19th century England to an Arctic expedition in 1960.
Rev. ed. of: Men and dinosaurs. 1st ed. 1968.
Includes bibliographical references (p. [265]-272 and index.
Science Books & Films (A.A.A.S.).
Young Adult
Keywords: Dinosaurs; Paleontologists; Dinosaurs; Paleontologists